Influence of Parents’ Care on Teenage Pregnancy in Imvepi Refugee Settlement, Terego District - Emmanuel Bangutu (Uganda Christian University, 2025)
This study examines the influence of parents’ support on teenage pregnancies in Imvepi Refugee Settlement, Terego District, Uganda. Additionally, the prevalence of teenage pregnancy remains among the major challenges faced by refugee settlements that have socially and economically vulnerable refugees. This paper discusses the contribution of parental care to the prevalence of teenage pregnancy among adolescents. The design of the qualitative research in this study involved semi-structured interviews carried out with the teenage respondents in the settlement. In this respect, such interviewees were asked to react to three stated objectives: how parental emotional care, financial care, and social care related to pregnancy status. Constrained financial situations and parents' inability to fulfill basic needs led teenagers into transactional relationships, hence making them have a higher risk of pregnancy. Inadequate parental social care, guidance, and supervision left a gap in supporting the adolescents in deciding and thus increased vulnerability. The study thus concludes that in refugee situations, parental involvement helps reduce teen pregnancy. It calls for reinforcement in the family support systems through community-based parenting programs, integrating the parental care intervention into current sexual and reproductive health education initiatives in refugee settlements. These could increase protective factors and reduce rates of teenage pregnancy in similar settings.
THESIS